Overcoming Immune Evasion in CAR-T Cell Therapy: Mechanisms and Coping Strategies for Clonal Evolution in Multiple Myeloma - Li, Hua; Zhu, Benben (Pacific International Journal, 2024)
This paper addresses the issue of immune evasion in CAR-T cell therapy, exploring the mechanisms underlying clonal evolution in multiple myeloma and proposing corresponding coping strategies. Overcoming these challenges necessitates a comprehensive approach, incorporating alternative therapeutic modalities and the advancement of next-generation CAR-T cell therapy. Furthermore, prioritizing in-depth investigations into drug resistance and immune evasion mechanisms, tailoring treatment strategies to individual patients, and conducting clinical trials and regulatory initiatives emerge as key focal points for future research. These endeavors are anticipated to propel the advancement of CAR-T cell therapy in multiple myeloma, offering enhanced treatment prospects for patients.